Türkiye’s Pivot to the East: Motivations and Key Challenges for Possible BRICS Membership - Özge Kotan (Uluslararası İlişkiler Çalışmaları Dergisi, 2025)
Türkiye's growing interest in BRICS highlights its eastward shifting foreign policy strategy of diversifying alliances in response to changing global power dynamics, a complex regional landscape and a challenging domestic political environment. This shift can be understood through the lens of strategic pragmatism, which remarks how Türkiye’s international alignments are shaped by domestic economic vulnerabilities and flexible, interest-based political calculations. In this regard, this article particularly focuses on economic motivations behind this interest. Türkiye's aspiration for BRICS membership is based on motives to establish alternative financial partnerships and to get support in dealing with its escalatingdomestic economic issues. These economic concerns are intertwined with the government's political ambitions to enhance the country's global standing and lessen reliance on Western institutions. Therefore, the article analyses the evolution of Türkiye's foreign policy over the decade and examines the appeal of BRICS as a strategy to provide pluralism for economic recovery and leverage for political power both internally and externally. Finally, it points out the challenges Türkiye may face on this path. These include structural issues, trade imbalances, and likely reactions from its Western allies due to its increased participation in non-Western power blocs.